2006
DOI: 10.1152/physrev.00015.2005
|View full text |Cite
|
Sign up to set email alerts
|

Function of cGMP-Dependent Protein Kinases as Revealed by Gene Deletion

Abstract: Over the past few years, a wealth of biochemical and functional data have been gathered on mammalian cGMP-dependent protein kinases (cGKs). In mammals, three different kinases are encoded by two genes. Mutant and chimeric cGK proteins generated by molecular biology techniques yielded important biochemical knowledge, such as the function of the NH(2)-terminal domains of cGKI and cGKII, the identity of the cGMP-binding sites of cGKI, and the substrate specificity of the enzymes. Genetic approaches have proven es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
336
1
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 358 publications
(347 citation statements)
references
References 311 publications
(344 reference statements)
7
336
1
3
Order By: Relevance
“…It had typical PKG domains (Hofmann et al, 2006) including a serine/threonine kinase domain (with a catalytic site) and two cGMPbinding domains. The same degenerate primers and techniques were used to clone the L. migratoria for ortholog lmfor (GenBank accession number FJ214984).…”
Section: The Locust Foraging Gene the Locust Foraging Genementioning
confidence: 99%
“…It had typical PKG domains (Hofmann et al, 2006) including a serine/threonine kinase domain (with a catalytic site) and two cGMPbinding domains. The same degenerate primers and techniques were used to clone the L. migratoria for ortholog lmfor (GenBank accession number FJ214984).…”
Section: The Locust Foraging Gene the Locust Foraging Genementioning
confidence: 99%
“…2, B and C). In this study, a PKG-I knockout mouse was not used due to its very limited lifespan (ϳ4 wk) (20).…”
Section: Renal Ir Injury Downregulates Kidney Pkg-i Levelsmentioning
confidence: 99%
“…In mammals, PKG is important for proper induction of long-term potentiation (LTP) and long-term depression (LTD) (Hartell 1994;Zhuo et al 1994;Lev-Ram et al 1997;Arancio et al 2001;Fiel et al 2003Fiel et al , 2005Kleppisch et al 2003;Hofmann et al 2006). Although LTP and LTD are thought to be important mechanisms underlying learning and memory (Whitlock et al 2006), few studies have shown a direct role for PKG in learning and memory.…”
mentioning
confidence: 99%